IMPROVING STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT OF VIII GRADE AT SMPN 3 TOLITOLI THROUGH SELF-QUESTIONING STRATEGY - Marzuki Marzuki (Universitas Madako Tolitoli, 2019)
The objective of the research is to find out whether the use of self-questioning strategy improve the students’ reading comprehension in narrative text.The design of this research is experimental research. The population of this researchis the eighth grade students of SMP Negeri 3 Tolitoli in the academic year of 2016/2017. The number of the subjects is 35 students. The data areobtain by administering reading test to the VIII B. The research is started by giving pre-test, treatments,and post-test. The data of the test areanalyze by using t-test formula to know the difference of the students’comprehension in reading narrative text. In the pre-test, the mean score of the experimental research is 49.34. The mean score of post-test of the experimental research is 83.20. The result of the t-test differenceis 11.848and t-table is2.032. It means that t-value is higherthan t-table (11.848>2.032). The calculation reveal that the hypothesis about asignificant difference on reading comprehension between students who arethrough narrative text by using Self-Questioning strategy.Based on the research conduct, it is prove that the use of Self-Questioning strategy is effective as a strategy to improve students’ Reading Comprehension In Narrative Text of VIII Grade At SMPN 3 Tolitoli. Key Words: Improve, Reading Comprehension,Self-Questioning strategy,Narrative text,